Parasitic Worm of Agile Gibbon (Hylobates agilis F. CUVIER 1821) and Siamang (Symphalangus syndactylus RAFFLES 1821) at Serulingmas Zoological Garden, Banjarnegara - Risa Tiuria; Putri Indah Ningtias; Hera Maheshwari (Universitas Airlangga, 2023)
Samples feces were collected from three heads of agile gibbon and three heads of siamang using direct smear, flotation, sedimentation, and McMaster methods. Identification is achieved by using faecal cultures to obtain larvae of parasitic worm. Identification result indicated that male agile gibbon (W/I) infected by two types of parasitic worms (Trichostrongylus and Strongyloides). In contrast, female agile gibbon (W/IIa and W/IIb), placed in the same cage as a male agile gibbon are uninfected by a parasitic worm. Male siamang (S/IA) put in a different cage with others is uninfected. Male siamang (S/IB) ia infected by three types of parasitic worms (Trichostrongylus, Strongyloides, and Cooperia) while the female siamang (S/IIB) that placed in the same cage with S/IB infected with one type of parasitic worm (Trichuris). Each egg account results showed no amount exceeding 300 eggs per gram of feces. This led to the degree of infection in agile gibbon and siamang at Serulingmas Zoological Garden, belonging to a common disease. It can be concluded that the type of parasitic worms found in the agile gibbon at Serulingmas Zoological Garden namely Trichostrongylus and Strongyloides while the variety of parasitic worms found in the siamang namely Trichuris, Trichostrongylus, Strongyloides, and Cooperia.